Reverse posterior interosseous flap for defects of the dorsal ulnar wrist using previously burned and recently grafted skin. Issue 2 (March 2016) - Baylan, Joseph M.; Chambers, J. Alan; McMullin, Neil; Fletcher, John L.; Sinha, Indranil; Lundy, Jonathan; King, Booker T.; Chan, Rodney K.
Highlights: Posterior interosseous artery (PIA) flaps can be utilized for dorsal hand coverage in burn patients. The PIA flap can include burned skin. PIA flap congestion or failure will necessitate reconstruction with other flap options. Abstract: Background: In the severely burned patient, coverage of exposed bone in the dorsal ulnar wrist can be a difficult problem. This is especially challenging in patients with a high percentage total body surface area (TBSA) where donor flaps can be scarce. The use of previously burned and/or recently grafted skin as flaps is an option. It has been postulated that use of previously burned skin can result in higher rates of local or distant flap failures. The reverse posterior interosseous flap (PIF) is an axial flap, based on the retrograde posterior interosseous artery, to provide coverage of the hand. Here we describe utilization of the PIF, using previously burned and/or recently grafted skin for coverage of dorsal ulnar wrist defects. Methods: This is a case series of three patients, with extensive burns (range 35–83%TBSA), where defects of the dorsal ulnar wrist necessitated coverage. Each patient underwent PIF(s) utilizing previously burned and/or grafted skin, all within three months after their initial burn event. Results: Case 1: 28 year old male who suffered 35% TBSA via blast mechanism developed a chronic open wound over the dorsal ulnar wrist with exposed tendon. The patient successfully underwent a left PIF using previously grafted skin. Case 2: 23 year old male with 83% TBSA. Bilateral ulnar styloids were exposed. PIFs were performed bilaterally, using previously burned and recently grafted skin. Coverage was successful but received leech therapy post-operatively for venous congestion. Case 3: 37 year old male with 52% TBSA, with the most severe burns isolated to his bilateral upper extremities; the ulnar head was exposed. The posterior interroseous artery was explored and PIF was attempted, but there was no retrograde flow in the distal artery due to a deeper injury than previously recognized. The patient ultimately underwent a pedicled abdominal flap for coverage. Conclusions: Defects of the distal ulnar wrist after deep and extensive burns can be problematic. Use of the reverse PIF using previously burned skin, even those that has just been recently grafted is a viable option for this difficult patient population. However, it may not be possible in all patients. Vigilance and early intervention for post-operative venous congestion are important.